(untitled) (Journal of Hama University, 2022)
This research is an overview of the continuation of the activity of the scientific movement in the Levant and Egypt, despite the bad conditions that the region experienced at that time.The research dealt with the factors of the activity of this movement and the political situation in the second half of the 17 th century AH/13 th century AD and the movement of the civilization and science from Baghdad to Damascus and its establishment in Cairo .Reference was made to scholars and the historical authorship movement at that time.